Impact of Ethics-Based Leadership, Organizational Conflict Management, Continuous Learning, and Employee Empowerment on Employee Performance - Guswati; Sumiati (Jurnal Informatika Ekonomi Bisnis, 2026)
This study aims to analyze the influence of ethics-based leadership, organizational conflict management, continuous learning, and employee empowerment on employee performance at Imam Bonjol State Islamic University, Padang, both partially and simultaneously. This study uses a quantitative approach with a survey method. The population in this study were all employees of Imam Bonjol State Islamic University, Padang, with a sample of 70 respondents determined using a total sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression analysis with the help of the SPSS program. The results of the study indicate that partially ethics-based leadership has a positive and significant effect on employee performance, organizational conflict management has a positive and significant effect on employee performance, continuous learning has a positive and significant effect on employee performance, and employee empowerment has a positive and significant effect on employee performance. Simultaneously, ethics-based leadership, organizational conflict management, continuous learning, and employee empowerment have a significant effect on employee performance. The coefficient of determination value of 0.650 indicates that 65% of the variation in employee performance can be explained by the four independent variables, while the rest is influenced by other factors outside the research model. The results of this study confirm that improving employee performance requires the implementation of ethical leadership, effective conflict management, strengthening a culture of continuous learning, and integrated and sustainable employee empowerment.